Ecological risk assessment and response prediction caused by LUCC in the central Yunnan Province - Yongdong Zhang; Zisheng Yang; Renyi Yang; Fuhua Liu; Yimei He; Linlin Cao; Jinrong Yang; Jiayi Zhang (Scientific Reports)
Abstract With the acceleration of urbanization, unreasonable land use poses a serious threat to ecological security. However, there is still some space for improvement in the existing assessment of ecological risks (ERs) caused by land use/land cover change (LUCC). Therefore, this study takes the central Yunnan Province (CYP) as an example, and uses the Patch-Generating Land Use Simulation (PLUS) model and the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model to simulate the land use/land cover (LULC) in different scenarios in the future, calculate the ecosystem services (ESs) from 2000 to 2020 and the next 20 years, as well as ERs of various types of ESs caused by LUCC. In addition, the Pearson correlation coefficient and geographically weighted regression (GWR) are used to analyze the trade-off and synergy relationships between various ecological risks, and the geographic detector method (GDM) is used to analyze their driving factors. The research results indicate that: (1) there have been significant changes in LULC in the CYP in the past 20 years. (2) There was significant spatial heterogeneity among various types of ESs in the CYP. (3) In the past 20 years, the distribution range of ERs has been relatively large, with significant spatial differences. (4) The ERs caused by LUCC in the next 20 years generally show a decreasing trend, and the ecological high-risk areas are mainly concentrated on construction land. (5) The ERs associated with ecosystem service types are mainly synergistic. ER is influenced by a combination of natural factors, socio-economic factors, and distance factors, with some factors having strong interactions. In short, the future ERs of CYP have decreased, and the ERs corresponding to various ecosystem services (ESs) interact with each other, causing a ripple effect. Finally, this study proposes policy recommendations to alleviate ERs in the CYP.